Pemberdayaan Masyarakat Desa Bukit Rawi, Kalimantan Tengah, melalui Pertanian Terpadu di Lahan Pekarangan - Apriliani, Yawia; Fitriani, Fitriani; Pajariah, Wiwit; Ramadani, Nia; Khairi, Khairi; Arifin, Samsul (LPPM Universitas Palangka Raya, 2024)
Bukit Rawi Village is one of the villages in the Kahayan Tengah District, Pulang Pisau Regency, Central Kalimantan Province. The village possesses natural resources including peat forests, rivers, and backyard gardens. Through the Organizational Capacity Strengthening Program (PPK Ormawa) of the Physics Student Association (HIMAFI), in collaboration with the target community, efforts are being made to develop agricultural potential by educating Bukit Rawi Village residents about farming practices. The implementation of agricultural empowerment begins with land cultivation, fertilization, fertilizer production, and vegetable farming in polybags. The methods employed include socialization, training, and continuous mentoring. The program aims to empower the community through the development of vegetable agriculture to enhance the welfare and progress of the village while maintaining forest conservation efforts. The program is carried out through training and mentoring aimed at improving knowledge of farming techniques, land management, composting, fertilization, application of natural pesticides, and the use of agricultural tools among the residents, all while ensuring forest preservation. It is hoped that the results of this activity can build a strong agricultural sector, increase community income, and maintain forest conservation efforts in Bukit Rawi Village.